Correlation between Serum Levels of Vaspin, BMI, and Waist Circumference on Obese and Non-Obese Subjects - Reskiana Syahrir; Nurahmi Nurahmi; Liong Boy Kurniawan (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
Obesity is the accumulation of excessive fat resulting from an imbalance in energy intake compared to energy used for a long period. Vaspin is secreted in adipose tissue and may exhibit compensatory responses related to obesity, insulin resistance, and type 2 diabetes mellitus. This study aimed to determine vaspin levels in obese and non-obese subjects.  An observational research design with a cross-sectional approach was used in this study. A total of 80 research subjects were included in this study. The research was conducted at the Clinical Pathology Laboratory at the Department of Clinical Pathology, Hasanuddin University Hospital in January 2022. Kolmogorov-Smirnov test was used to determine the normality of the data. Chi-Square, unpaired T-test, Mann-Whitney test, and Spearman test were used as statistical tests. This study showed a significant difference in anthropometric parameters between the obese and non-obese groups (p < 0.001). There was a significant difference in the mean levels of vaspin between the obese and non-obese groups (707.68±774.47 ng/mL vs. 510.60±460.08 ng/mL, p=0.004). There was a positive correlation between vaspin levels and waist circumference (r = 0.245, p=0.004) and between vaspin levels and BMI (r = 0.322, p=0.028). The serum levels of vaspin tended to be higher in obese subjects compared to non-obese subjects. The positive correlation between vaspin levels and BMI and waist circumference indicated that a higher BMI and/or waist circumference led to a higher vaspin level.